ANALISIS BAHAN BAKU DEPOT AIR MINUM ISI ULANG DARI PERSPEKTIF ETIKA BISNIS SYARIAH: STUDI PADA DEPOT AIR MINUM ISI ULANG DI KELURAHAN KENALI ASAM BAWAH KOTA JAMBI (Lembaga Pengembangan Kinerja Dosen, 2023)
The results this study were analyzed using the inductive method, namely the process thinking from empirical facts obtained from the field (in the form field data) which were then analyzed, interpreted and ended with conclusions on problems based on the field data. From this study it can be concluded that the process producing refill drinking water is appropriate and some is not in accordance with the principles Islamic business ethics, because business actors do not routinely replace refill drinking water filters and ultraviolet lamps. Apart from that, in the production refill drinking water, there are also several depots that violate Islamic business ethics in the production process, namely the prohibition production which leads tyranny. While the process selling refill drinking wateR appropriate and some are not accordance with the principles Islamic business ethics where some depots do not provide clear information regarding water quality, and stock drinking water refills in gallons. Apart from that, in the sale refill drinking water, there are those who violate Islamic business ethics in the sales process, namely the prohibition gharar and tadlis.